Geopolitics in late antiquity - Kim, Hyun Jin, 1982- author.
1 online resource.
Keywords: "Geopolitics in Late Antiquity explores the geopolitical revolution which shook the foundations of the ancient world, the dawning of the millennium of Inner Asian dominance and virtual monopoly of world power (with interludes) that began with the rise of the Huns and then continued under the hegemony of various other steppe peoples. Kim examines first the geopolitical situation created by the rise of Inner Asian powers, and then the reactions of the great empires of Eurasia to this geopolitical challenge. A unique feature of this book is its in-depth analysis of the geo-strategies (some successful, others misguided) adopted by China, Rome and Persia to cope with the growing Inner Asian threat. The conclusions and insights drawn from this analysis are then used to inform modern geopolitics, mainly the contest for hegemonic power between the United States and China. Geopolitics in Late Antiquity is a crucial resource for both academic and learned general readership, who have an interest in the fate of antiquity's superpowers and also for those engaged in current international relations policy-making, who wish to learn from historical precedents"--